Tourist image of Spain - Alina A. Koroleva (Ибероамериканские тетради, 2016)
He article touches upon one of the elements of the “soft power” of Spain - tourism; gives a brief overview of the scale advertising campaigns; presents the basic stereotypes associated with tourist Spain